2016
DOI: 10.1111/joss.12216
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Menu Label Design on Visual Attention, Food Choice and Recognition: An Eye Tracking Study

Abstract: Nutritional labelling on menus has been found to promote informed food choices and reduce information asymmetry between manufacturers and consumers. However, lack of attention to nutritional labels limits their effectiveness. This study manipulated the way in which nutritional information was provided on menus in aim of enhancing visual attention to the most health relevant information. A between-subject design was implemented with three experimental conditions (non-directive label; directive label; semi-direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 76 publications
2
27
0
Order By: Relevance
“…Yang, 2012). Eye-tracking research on restaurant menu labelling was undertaken primarily in the context of nutritional information (Kim et al, 2018;Reale & Flint, 2016;Schwebler, Harrington, & Ottenbacher, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Yang, 2012). Eye-tracking research on restaurant menu labelling was undertaken primarily in the context of nutritional information (Kim et al, 2018;Reale & Flint, 2016;Schwebler, Harrington, & Ottenbacher, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Yoon et al studied liking, emotional response, and the appropriate intensity of attributes of beverages when consumers were provided with information about the beverages, including nutritional information [7]. Further, Reale and Flint studied how providing nutritional information affected the selection of products on a menu, and showed that the graphical qualities rather than the specific information were more important [8]. Consumer attitudes toward product-related information are important factors to consider because they will determine the acceptance of food products, and the final decision of product purchase.…”
Section: Introductionmentioning
confidence: 99%
“…Put together, these results collectively suggest that ethnically congruent music can invariably impact consumer choice as well as visual attention in both Western and Eastern cultures, possibly by creating referential meaning through semantic connotations. On a broader level, our findings demonstrate that not only extensively studied extrinsic product factors such as packaging and label design [33,59], but also contextual, ambient stimuli unrelated to the product itself can influence consumers' visual attention.…”
Section: Discussionmentioning
confidence: 76%